The pursuit of Covid-19 animal models - Abdul Rahim, Roslina; Muhammad, Siti Aeshah @ Naznin (IIUM Press, 2020)
Coronavirus disease 2019 (COVID-19) is a contagious disease instigated by a recently discovered coronavirus, the 2019 novel coronavirus (2019-nCoV). It has infected over 14 million people worldwide from all age groups. This virus is conveyed through big droplets produced during coughing and sneezing by the infected individuals. COVID-19 precipitates acute respiratory distress syndrome which leads to morbidity and mortality in severe cases. To date, there is neither an established specific antiviral treatment for COVID-19, nor vaccine available. Preventive measure of social distancing is deemed to be the most effective way to avoid the spread of the virus. Scientists are currently in search of appropriate COVID-19 animal models for use in research works related to pathogenesis, potential drug treatments and vaccine development. This review delivers a pithy overview of the currently available COVID-19 animal models published in the literatures.